Assessment of pollution and sources of heavy metals in the sediments of the Shitalakhya river, Bangladesh - Rahman, Kalimur; Barua, Saurav; Ahammad, Fahim; Akramul Alam, Md. (International Journal of Advanced Geosciences, 2020)
The Shitalakya River, located near Dhaka City of Bangladesh, supplies water to the city dwellers and hence it is essential to determine pollu-tion condition, ecological risk and sources of heavy metals in the river sediments. Sediment works as the sink and source of heavy metals in the riverine ecosystem. The samples collected from the ten sites of the Shitalakhya River were investigated in the study. Average concentra-tion of different heavy metals in the sediments are Cu>Zn>Ni>Pb>Cr>Cd. Geo-accumulation index reveals moderately pollute Cu concen-tration, unpolluted to moderately pollute Ni concentration and unpolluted for the rest of the heavy metals. The order of geo-accumulation index are Cu>Ni>Pb>Cd>Zn>Cr. Overall, the heavy metals render low potential ecological risk and the order of potential ecological risk index are Cd>Cu>Ni>Pb>Cr>Zn. Though the concentration of Cd is low in sediment, it poses higher ecological risk. Positive matrix factor-ization (PMF) identifies two sources of pollution, S1 and S2. Where, S1 consists with Cu, Ni, Pb, Zn; which come from industrial wastewater. S2 consists with Cr, Cd, Pb, Zn; which originate from natural sources. The outcomes of the study provide as a reference to plan, control and manage heavy metal pollution and protect the water source of the Shitalakhya River.Â Â Â Â